A model linking HRM practices, service-oriented OCBs & organizational performance in Malaysian hotel industry / Lee-Yen Foo … [et al.] - Foo, Lee-Yen; Ghazali, Hazrina; Zawawi, Dahlia; Mohamad, Siti Fatimah; Othman, Mohhidin (Universiti Teknologi Mara Selangor, 2019)
Customer contact employees are the major and direct interface contact with existing and potential customers of hotels. Customer contact employees’ behaviours and service performance are factors for a hotel to be successful. Hotels have to pay a great attention on the human resource management (HRM) practices and manage their customer contact employees’ behaviours which ultimately encourage them to provide better service quality and improve organizational performance. Therefore, the purpose of this study is to examine a model linking HRM practices, employee satisfaction, service-oriented organizational citizenship behaviours (OCBs), customer satisfaction and organizational performance in hotel industry in Malaysia. A cross-sectional survey was conducted with human resource managers, customer contact employees and customers in upscale hotels (with 4- and 5-star ratings) in Malaysia. A two-stage sampling technique was employed in which stratified sampling was used in choosing the hotels and purposive sampling was used in choosing the respondents. The data collected were analysed using the structural equation modelling analysis to examine and explain the relationships hypothesized in the proposed model. The statistical results obtained provide support to the proposed model. The findings reveal that HRM practices significantly influence employee satisfaction which in turn significantly influences service-oriented OCBs and sequentially determine organizational performance. The findings of this study are believed to provide better understanding and knowledge for the management of hotels about the linkage of HRM practices, employee satisfaction, service-oriented OCBs, customer satisfaction and organizational performance in the hotel industry in Malaysia.